2021
DOI: 10.3390/vaccines9050516
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Perceptions of COVID-19 Vaccination among Healthcare Workers of an Inner-City Hospital in New York

Abstract: Introduction: New York City is one of the areas most affected by the COVID-19 pandemic in the United States. Healthcare workers are among those at high risk of contracting the virus, and a vital source of information and trust in vaccines to the community. Methods: This study was conducted about attitudes towards COVID-19 vaccination among healthcare workers at a public hospital in New York City during the beginning of COVID-19 vaccination. 428 hospital employees responded. Results: Several factors were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 22 publications
9
85
4
Order By: Relevance
“…A lower acceptance was obtained in nurses (61%) compared with the general population (75%) and doctors (78%) (22). These results are in line with a study conducted in the United States, where nurses and patient care associates were among those with the least intended to be vaccinated in comparison to medical students and physicians who were the highest (23).…”
Section: Refsupporting
confidence: 85%
“…A lower acceptance was obtained in nurses (61%) compared with the general population (75%) and doctors (78%) (22). These results are in line with a study conducted in the United States, where nurses and patient care associates were among those with the least intended to be vaccinated in comparison to medical students and physicians who were the highest (23).…”
Section: Refsupporting
confidence: 85%
“…The data from individual cross-sectional surveys across individual (or multiple) USA states report different rates of vaccine hesitancy/acceptance, however, they do differ in the time periods when they were conducted and the populations they surveyed. For example, two surveys conducted in New York state covering healthcare workers found lower willingness among this population in December [82] compared with the data collected in December 2020/January 202,1 [83] when vaccination had already begun; however, it should be noted that the difference in sample size was considerable. The later study also observed an increase in willingness if the surveyed population had the option to consider vaccination in the future.…”
Section: Resultsmentioning
confidence: 71%
“…Two noteworthy concerns revealed by this review were that HCPs have low vaccination rates, as previous studies observed [ 134 , 142 ], and many have insufficient knowledge about vaccines or the diseases they prevent [ 143 ]. Educational goals should include increasing both HCPs’ competency in vaccine education and their own vaccine acceptance.…”
Section: Discussionmentioning
confidence: 91%